Growth and Non-Specific Immune Responses of Asian Seabass (Lates calcarifer) Fed on Commercial and Mixed Pure Nucelotides Diet - Hastuti, Sri Dwi; Munro, James; Pyecroft, Stephen (Aquacultura Indonesiana, 2016)
Asian seabass (Lates calcarifer) aquaculture is potential developing industry in Australia and Indonesia. As the aquaculture industry intensifies, the occurrence of significant diseases becomes more likely. Hence, it is important to find better methods for controlling diseases in this industry. Research on mammals and fish have previously demonstrated the potential benefits of dietary nucleotides to enhance immune function of the animal to combat diseases. However there is still very limited study of this subject in  Asian seabass. This study aims to investigate the role of dietary nucleotides on the growth and immune responses of Asian seabass. Juvenile Asian seabass with average weight of 13.8±1.29 (mean ± SD) g were fed three different diets containing either Optimun® nucleotides or a mix of pure nucleotides at 0.25% per kg feed and one basal diet (nucleotide free diet). Fish were fed at 3 % BW per day for 28 days. Results showed that dietary nucleotides did not significantly effect the growth, survival rate, and immune responses of the fish. However  Optimun® diet gave higher result in terms of growth, leucocrit level, lysozyme activity and respiratory burst activity of head kidney leucocyte compare to basal and the mix of pure nucleotide diets.